Study on soil analysis in ponds in the Sabang block areas, West Bengal, India - Kumar Maji, Uttam; Ranajit Kumar Khalua; Maiti, Kartik (International Journal of Scientific Research in Biological Sciences, 2019)
Bacteria live in fresh water, soil, air and sea water. Bacteria have different nature in different zone. Thus periphyton bacteria has different characteristic in different zone. But I discussed in my topic soil analysis in fresh water ponds in Sabang block areas. I have done the experiment about one year in Sabang block areas. Soil collected by the bucket. This collected soil is collected from five ponds (Ghat pond, Dhara pond, Majari pond, Nandan pond & Masanta pond) in Sabang block areas. There were two types of pond present Control pond and Experimental pond. In this pond was added the semidried cow dank. In this experiment we are followed the some methods. The pond bottom soil was analyzed for nitrogen, available phosphorus and available potassium following the standard methods of AOAC (1980). In all the experimental ponds before treatment however, after treatment the nitrogen level increased considerable. Phosphorus plays significant role in enhancing the productivity of pond. Potassium is not limiting factor and is not necessary to increase production